Model Numbered Heads Together (NHT) Sebagai Upaya Meningkatkan Pemahaman Materi Pendidikan Pancasila Siswa - Azzahra, Fahira; Camellia, Camellia (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the effect of the Numbered Heads Together (NHT) learning model on improving students’ understanding of Pancasila Education material among eleventh-grade students at SMA Negeri 1 Indralaya Selatan. The research employed a quantitative approach with a One-Group Pretest-Posttest Design. The sample consisted of 34 students from class XI.F5 selected through purposive sampling. Data were collected through tests, observations, and documentation. The results showed a significant improvement in students’ average scores, from 41 on the pretest to 84 on the posttest. The Paired Sample T-Test result indicated a significance value (Sig. 2-tailed) of < 0.001 (< 0.05), meaning that the NHT model significantly influenced students’ comprehension improvement. These findings suggest that the NHT learning model effectively enhances students’ conceptual understanding, individual and group responsibility, and critical thinking skills in Pancasila Education learning.